2020
DOI: 10.1590/s1678-3921.pab2020.v55.00708
|View full text |Cite
|
Sign up to set email alerts
|

Extended use of poultry manure as a nutrient source for flood-irrigated rice crop

Abstract: How to cite SCHmIdt, F.; KNoBlAuCH, R. Extended use of poultry manure as a nutrient source for floodirrigated rice crop. Pesquisa Agropecuária Brasileira, v.55, e00708, 2020. doI: https://doi. Abstract -The objective of this work was to evaluate changes in the soil chemical properties, nitrogen use efficiency, and grain yield of flood-irrigated rice fields after the addition of poultry manure during five years. Trials were carried out in a randomized complete block design, with three replicates. The treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…In this study, nutrient contents of grain and straw of all genotypes showed that the highest N, P, and K contents were recorded in T 2 (2.5 t ha −1 CM+ 50% CFRR). These findings are partially similar to these of [50,51], who obtained higher contents of nutrient elements such as N, P, and K in rice by applying chicken manure with inorganic fertilizers. The use of a combination of organic manures and inorganic fertilizers clearly aided plant vegetative growth, resulting in higher straw yield.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, nutrient contents of grain and straw of all genotypes showed that the highest N, P, and K contents were recorded in T 2 (2.5 t ha −1 CM+ 50% CFRR). These findings are partially similar to these of [50,51], who obtained higher contents of nutrient elements such as N, P, and K in rice by applying chicken manure with inorganic fertilizers. The use of a combination of organic manures and inorganic fertilizers clearly aided plant vegetative growth, resulting in higher straw yield.…”
Section: Discussionsupporting
confidence: 87%
“…In case of straw, treatment combination PM × T 4 had the highest N (0.66%), P (0.18%), K (1.34%), and S (0.08%) content and the treatment combination CD × T 0 had the lowest N (0.36%), P (0.0.08%), K (0.63%), and S (0.03%) content. These results are somewhat similar to those of Schmidt and Knoblauch [54]; Moe et al [55], who applied poultry manure along with inorganic fertilizers to increase the concentration of nutrients including N, P, K and S in rice. The application of both inorganic and organic fertilizers clearly enhanced plant vegetative growth and increased the yield of straw [1].…”
Section: Plant Nutrient Concentrationsupporting
confidence: 88%
“…PM has a high organic content (559.30 g kg−1) which slowly releases nutrients into plants to improve and increase the chemical and physical properties of the soil [34]. It is relevant to other previous studies, such as that of Schmidt and Knoblauch [35], who reported that PM contained 2.44% N, 0.67% P, 1.24% K, and C-organic 16.10% and was good for cabbage in Oxic Dystrudepts Lembantongoa. Moe et al [36] also reported that chicken manure contained 4.87% N, 4.56% P, and 2.14% K, while Soe et al [37] reported that highest P, K, Ca, and Mg contents in PM were 2.07%, 1.24%, 6.55%, and 0.70%, respectively.…”
Section: Karst Dryland Characteristictsmentioning
confidence: 99%